2020
DOI: 10.1080/16000889.2020.1803708
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol carbonaceous, elemental and ionic composition variability and origin at the Siberian High Arctic, Cape Baranova

Abstract: Aerosol particles are major short-lived climate forcers, because of their ability to interact with incoming solar radiation. Therefore, addressing mean levels and sources of Arctic aerosols is of high importance in the battle against climate change, due to the Arctic amplification. In the Eastern Arctic, from Finland to Alaska, only one monitoring station exists (HMO Tiksi) and the levels of the Arctic aerosols are usually recorded by sporadic campaigns, while other stations exist in Canada, Finland and Europe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 60 publications
(91 reference statements)
0
6
0
Order By: Relevance
“…As many studies have shown in the past, air pollution is a significant problem due to the multiple effects it has on human health, the environment [1][2][3], and climate [4]. Many resources and effort have been spent to reduce the particulate matter (PM) concentration levels and, consequently, their effects on human health and understand their behavior and properties in different environments [5,6]. Human health effects associated with PM pollution are premature death, hospital admissions, emergency room visit, asthma attack, chronic bronchitis, cancer, cardiovascular disease, diabetes, and restricted activity [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…As many studies have shown in the past, air pollution is a significant problem due to the multiple effects it has on human health, the environment [1][2][3], and climate [4]. Many resources and effort have been spent to reduce the particulate matter (PM) concentration levels and, consequently, their effects on human health and understand their behavior and properties in different environments [5,6]. Human health effects associated with PM pollution are premature death, hospital admissions, emergency room visit, asthma attack, chronic bronchitis, cancer, cardiovascular disease, diabetes, and restricted activity [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Eleftheriadis et al (2009) and Tunved et al (2013) identified these regions as a key source for the highest measured BC concentrations and sub-micrometer aerosol mass concentrations, respectively, at Zeppelin station. The impact of BC long-range transport from northwestern Siberia was also observed at Ice Base Cape Baranova station located on Severnaya Zemlya archipelago (eastern Siberia) (Manousakas et al, 2020). Accordingly, possible gas flaring impact was observed at Tiksi station (northeastern Siberia) despite the large distance of the station from the largest oil and gas producing regions (Winiger et al, 2017).…”
Section: Introductionmentioning
confidence: 83%
“…(Eleftheriadis et al, 2009) and (Tunved et al, 2013) identified these regions as a key source for the highest measured BC concentrations and sub-micrometer aerosol mass concentration, respectively, at the Zeppelin station. The impact of BC long-range transport from northwestern Siberia was also observed at the Ice Base Cape Baranova station located on Severnaya Zemlya archipelago (Eastern Siberia) (Manousakas et al, 2020). Accordingly, possible gas flaring impact was observed at the Tiksi station (northeastern Siberia), despite the large distance of the station from the largest oil and gas producing regions (Winiger et al, 2017).…”
Section: Introductionmentioning
confidence: 88%
“…Simulations combined with observations of BC at the proximity of the source regions (e.g., the plumes from gas flaring regions over the Kara Sea) provide a better consistency (Popovicheva et al, 2017). In addition, measurements of BC coupled by conditional probability simulations performed at the Polar circle inside the oil and gas producing region of the northwestern Siberia have successfully separated the multiple industrial and urban sources (Popovicheva et al, 2020). (Huang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%